4.4-μm Raman laser based on hollow-core silica fibre. (June 2017) - Gladyshev, A.V.; Kosolapov, A.F.; Khudyakov, M.M.; Yatsenko, Yu.P.; Kolyadin, A.N.; Krylov, A.A.; Pryamikov, A.D.; Biriukov, A.S.; Likhachev, M.E.; Bufetov, I.A.; Dianov, E.M.
Abstract: A Raman laser with a wavelength exceeding 4 μm is designed for the first time. Using a revolver silica fibre with a hollow core filled with molecular hydrogen ( 1 H2 ) as an active medium, we have obtained SRS lasing at a wavelength of 4.4 μm under pumping by a pulsed erbium fibre laser ( λ = 1.56 μm, τ = 2 ns). The SRS conversion quantum efficiency reaches 15 %, and the maximum output peak power at a wavelength of 4.4 μm is 0.6 kW.